The Profitability And Financial Feasibility Analysis Local Chicken Slaughter Business At Ragawi Farm - Raihan Khalifah Rahman; Amelia Murtisari (UNIVED Press, Dehasen University Bengkulu, 2026)
Purpose: This study aims to analyze the profits earned by farmers and assess the financial feasibility of the local chicken slaughter business at Ragawi Farm in Sleman Regency. Methodology: This study uses a descriptive analysis method with a quantitative approach and a case study research type. The data used consists of primary and secondary data obtained through interviews, literature studies, documentation, and questionnaires. Data analysis was carried out by calculating the total profit and assessing financial feasibility using the Revenue Cost Ratio (R/C), Net Benefit Cost Ratio (Net B/C), Break Even Point (BEP), and Net Profit Margin (NPM) methods. Results: The local chicken slaughter business at Ragawi Farm generated a profit of IDR 50,495,370 over nine periods. The R/C value of 1.67 and the B/C value of 0.67. The break-even point (BEP) was 507 chickens, with a BEP value of Rp33,455,577, and the Net Profit Margin was 40%. Findings: The local chicken slaughter business at Ragawi Farm in Sleman Regency has been declared feasible. Novelty: Financial feasibility analysis of local chicken slaughter business integrated with breeding and slaughterhouse activities (RPA) in a single business unit at Ragawi Farm. Originality: A specific case study on the Kampung Unggul Balitbangtan (KUB) local chicken business at Ragawi Farm, Sleman Regency, which has not been widely studied in previous research. Conclusion: The local chicken slaughter business at Ragawi Farm is profitable for farmers and worth developing from a financial perspective. Type of Paper: Research Article.